Effect of infaq and takmil wal istikmal in sustaining community vegetable farming in Malaysia - Sarif, Suhaimi Mhd (IKAZ ACIS UITM, 2019)
Infaq or charitable contribution is important activity in community. The spirit of togetherness in making community projects beneficial to the community is essential force in sustaining the welfare and wellbeing of community. Community vegetable farming allows community members to collaborate, cooperate and complement. This community vegetable farming has been practiced among traditional farmers of vegetables and fruits together with members of the community. The cooperation among farmers and community on complementarity basis is linking them to takmil wal istikmal in sustaining responsible consumption and production. Mass vegetable and fruits farming with modern farming approach contributes to unhealthy vegetable and fruit consumption. When vegetable farmers and non-farmers are working on common objective that is to have fresh and organic vegetables and fruits, they will cooperate, complement and consolidate relationships. The effect of infaq sustains both financial and non-financial supports. As for the effect of takmil wal istikmal is in the planning, implementation and evaluation of the community vegetable farming. This study investigates the effect of infaq and takmil wal istikmal complementarity in sustaining community support agriculture (CSA) with farmers and stakeholders. The study employs personal interview with selected farmers, administrators of community support agriculture and regulators of agriculture in Malaysia. The interview results show that there effect of infaq and takmil wal istikmal is limited to small scale of community farming.